STUDENTSâ SCHEMATA ACTIVATION IN EXTENSIVE READING AT STAIN PONOROGO - Susilo, Andi; Ahmadi, Ahmadi; Widiyawati, Wiwin (Kodifikasia, 2013)
This study was aimed at investigating the extent to which the lecturer employedstrategy and occupied effective classroom language to assist studentsâ schemataactivation on Extensive Reading class at English Department-STAIN Ponorogo. Tomeet with the objectives, qualitative case study formed the methodological basis ofthis present research involving an extensive reading lecturer as the researchsubject with one of her respective classes consisted of 32 students of fourthsemester. The data were derived from lecturerâs utterances (verbal) and bodylanguage (nonverbal). Those data were obtained from the transcripts of therecorded lecturerâs utterances during two periods of meeting, and note-takingtaken from observations and interviews. The results revealed that the lecturer usedto employ questioning technique to activate studentsâ schemata. Various strategieswere predominantly occupied in lecturerâs questioning behaviors to engagestudents in question-answer activities, such as probing, redirecting andreinforcement. Generally, those strategies were observed not only to providemotivation and focus studentsâ attention towards the topic being discussed, but alsoto give a wide chance of opportunity for them to recall their prior knowledge andease them to predict the content of reading texts they were going to read. Besides,the language the lecturer used under this investigation was fairly fulfilled therequirements to be communicative as some communicative features of talks wereutilized properly, such as referential questions, content feedback, and speechmodification to optimize students participation and performance in the process ofreading.